Defining isoscapes in the Northeast Pacific as an index of ocean productivity. Issue 2 (12th November 2019) - Espinasse, Boris; Hunt, Brian P. V.; Batten, Sonia D.; Pakhomov, Evgeny A.
Abstract: Aim: We modelled isoscapes in the Northeast (NE) Pacific using satellite‐based data, with the main objective of testing whether isoscapes defined by a few key parameters can be used as a proxy for secondary productivity. Location: Northeast Pacific; 46–60° N and 125–165° W. Time period: From 1998 to 2017 (ongoing). Major taxa studied: Zooplankton, with a focus on large herbivores. Methods: Approximately 280 summer zooplankton samples were analysed for carbon (δ 13 C) and nitrogen (δ 15 N) stable isotope (SI) ratios. Environmental conditions experienced by zooplankton organisms were extracted from satellite, in situ sensor and model databases. A generalized additive model approach was used to explain the spatial variability of δ 13 C and δ 15 N values and to predict isoscapes. Results: Sea surface temperature (SST), sea level anomaly (SLA) and chlorophyll‐ a concentration emerged as the significant SI predictors. Modelled isoscapes reproduced patterns observed in δ 13 C and δ 15 N value distribution, such as a decrease from the coast to offshore. The contribution of eddies in enhancing local production in the open ocean was also well captured by the models. In the central part of the NE Pacific, higher SI values were correlated with higher large copepod biomass measured by the North Pacific Continuous Plankton Recorder (CPR) survey. However, in the area off the coast of British Columbia, high δ 15 N variability appeared to be associated with episodic intrusions of coastal waters, demonstrating that caution is needed when interpreting sharp changes in SI ratios. Main conclusions: Although the mechanisms driving SI ratio variability are complex, we demonstrate that a few parameters used as a proxy for some of these major mechanisms are able to produce successful isoscape models. This approach was proved useful to provide a qualitative estimate of secondary production, which can be particularly valuable in a region where few data are available.